Which serum markers predict the success of reimplantation after periprosthetic joint infection? - Hongyi Shao; Tao Bian; Yixin Zhou; Yong Huang; Yang Song; Dejin Yang (Journal of Orthopaedics and Traumatology, 2022)
Abstract Purpose In clinical practice, serum C-reactive protein (CRP) and erythrocyte sedimentation rate (ESR) levels are routinely used to screen for periprosthetic joint infection (PJI), but the effectiveness of predicting the success of reimplantation is variable. This study aimed to evaluate the diagnostic effectiveness of serum CRP, ESR, plasma D-dimer, and fibrinogen values in groups achieving treatment success or failure for PJI. Methods A total of 119 PJI cases between January 2012 and January 2017 were identified and included in this study. The most recent serum CRP, ESR, plasma D-dimer, and fibrinogen values obtained prior to performing second-stage revision or spacer exchange were collected for analysis. Treatment failure was defined as having been unable to undergo reimplantation due to clinically persistent infection or reinfection after reimplantation. Results All these tests showed significantly lower values in the treatment success group than in the treatment failure group. The optimal cutoff serum CRP, ESR, plasma D-dimer, and fibrinogen levels for predicting the success of reimplantation were 9.4 mg/L, 29 mm/h, 1740 ng/mL, and 365.6 mg/dL, respectively. All tests had the same sensitivity (72.7%) except for ESR (63.6%), while their specificities were 92.6%, 88.0%, 72.3%, and 83.2%, respectively. Plasma fibrinogen had the highest AUC value of 0.831 [95% confidence interval (CI), 0.685 to 0.978], followed by serum CRP (0.829) and ESR (0.795); plasma D-dimer had the lowest AUC value of 0.716 (95% CI, 0.573 to 0.859). Conclusion Plasma CRP and fibrinogen are good tests for predicting reimplantation success after two-stage revision procedures for patients with PJI.